Pedagogical aspects of digital professional teaching skills development - Victoria V. Levchenko; Elena V. Zharkikh; Olga A. Mironova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The school teachers’ professional development requires systematic approach and innovation in the context of 2017 professional standardized profile. This paper highlights the lack of sufficient practical experience of work within the framework of new standard and a clear performance of the teachers’ training professional development. The article reveals the notion and pedagogical bases of new professional skills development of secondary school teachers, the main approaches to the process of formation of professional skills, their digital education and technological awareness as well as their main components and categories that characterize that process in the context of the problem of changing the paradigm of modern education. The findings of the research illustrate how the teachers’ training professional development can be based on the algorithm, which allows transforming the acquired skills into the ability to apply them in new, changing conditions.